A comparative evaluation of EEG Power spectrum characteristics between two methods for alleviating preoperative anxiety in breast cancer patients - Xing Jin; Yuxing Wang; Hui Jiang; Ying Wu; Yi Liu (Frontiers in Psychiatry)
IntroductionWomen with breast cancer are prone to moderate to severe preoperative anxiety. Effective measures for preventing and managing preoperative anxiety include drug therapy and non-drug intervention. The main evaluation method is scale assessment, which has certain limitations and may involve human concealment or evaluation errors. In this study, resting-state electroencephalography (EEG) was used to explore changes in power spectrum during the alleviation of preoperative anxiety in breast cancer patients, which is of great significance for objectively identifying and evaluating preoperative anxiety in patients.Methods40 breast cancer patients were randomly divided into two groups (20 patients per group), receiving either psychological intervention (PI) or intravenous midazolam (MID) before surgery. Visual Analog Scale for Anxiety (VAS-A) and Observer’s assessment alert/Sedation (OAA/S) scores, clinical monitoring indexes and EEG data were measured before and after intervention.ResultsVAS-A scores significantly decreased in both groups (p < 0.05), the power in the theta band of the frontal parietal regions decreased (p < 0.05) and was positively correlated with VAS-A scores (p < 0.001). Network analysis revealed that the three highest centrality measures in the PI group were located in the alpha band frontal parietal region, frontal central region, and gamma band parietal region, while the OAA/S scores showed the highest centrality for all three measures in the MID group.ConclusionsBoth PI and intravenous MID can effectively alleviate preoperative anxiety in breast cancer patients, but their neuroelectrophysiological mechanisms were not entirely the same. Regarding the relationship between brain region power and monitoring indexes, the power of three specific regions in certain frequency bands was the primary factor in the PI group, while the level of sedation was the determining factor in the MID group.